SDF-1/CXCR4 expression is an independent negative prognostic biomarker in patients with head and neck cancer after primary radiochemotherapy - De-Colle, Chiara; Abdollahi, Amir; Debus, Jürgen; Baumann, Michael (Radiotherapy and oncology, 2018)
Introduction: Preclinical and clinical data suggest that the chemokine pathway governed by SDF-1 and CXCR4 contributes to a resistant phenotype. This retrospective biomarker study aims to explore the speciﬁc prognostic value of SDF-1 and CXCR4 expression in locally advanced head and neck squamous cell carcinomas (HNSCC) treated with primary radiochemotherapy (RT-CT). Material and methods: Biopsies from 141 HNSCC tumours of the oral cavity, oropharynx and hypopharynx were evaluated for SDF-1 and CXCR4 expression by immunoﬂuorescence. SDF-1 and CXCR4 expression was correlated with clinico-pathological characteristics and outcome after RT-CT.Results: Patients with tumours exhibiting overexpression of intracellular SDF-1 and CXCR4 have a higher risk for loco-regional relapse and a worse overall survival after RT-CT (multivariate analysis, hazard ratio 2.33, CI [1.18-4.62], p = 0.02 and hazard ratio 2.02, CI [1.13-3.59], p = 0.02, respectively). Similar results were observed when only the subgroup of HPV DNA negative patients were analysed (hazard ratio 2.23 and 2.16, p = 0.02 and p = 0.01, respectively).Conclusions: Our data support the importance of SDF-1 and CXCR4 expression for loco-regional control and overall survival in HNSCC after primary radiochemotherapy. Prospective multivariate validation and further studies into CXCR4 inhibition to overcome radiation resistance are warranted.
Available online 20 October 2017
Gesehen am 10.10.2018